Fractional superLie algebras and groups - Ahmedov, H; Yildiz, A; Ucan, Y (IOP PUBLISHING LTD, 2001)
The nth root of a Lie algebra and its dual (that is the fractional supergroup) based on the permutation group S-n invariant forms is formulated in the Hopf algebra formalism. Detailed discussion Of S-3-graded sl(2) algebras is performed.
Keywords: SUPERSYMMETRY; ROOTS; UNITY; Physics